GAYA KEPENGARANGAN DEWI LESTARI DALAM NOVEL SUPERNOVA: KESATRIA, PUTRI, DAN BINTANG JATUH - Vera Soraya Putri; Endang Sri Widayati; Furoidatul Husniah (Komposisi: Jurnal Pendidikan Bahasa, Sastra, dan Seni, 2019)
Dewi Lestari has a distinctive authorship in Supernova: Kesatria, Putri, dan Bintang Jatuh novel. This particularity can be seen in the construction of content and the use of linguistic aspects as a means of delivering ideas by Dewi Lestari. This research aims to describe the construction of themes and characters, and the form of linguistic aspects as Dewi Lestari's authorship in the Supernova: Kesatria, Putri, dan Bintang Jatuh novel. This research used descriptive-qualitative, and used stylistic approach. The finding of the research showed Dewi Lestari's authorship style in Supernova: Kesatria, Putri, dan Bintang Jatuh novel is "humanist, using telling-showing perspective duality method, scientific-futuristic lexical categories, and figurative language as a functional aesthetic". The results of the themes construction, showed that Supernova: Kesatria, Putri, dan Bintang Jatuh novel had a humanist style. Dewi Lestari constructs the characters using telling-showing perspective duality method. The linguistic aspect used by Dewi Lestari is a lexical scientific-futuristic pattern, and figurative language as a functional aesthetics. The results of this study can be used as an alternative literature learning material in 12th grade of high school. The utilization of the results of stylistic research as an alternative to literary learning material is the implementation of collaboration in understanding aspects of novel content and language as an effort to improve language skills.